CAN GREEN HRM AND HEALTH & SAFETY PAVE THE WAY FOR BETTER PERFORMANCE? - Evi Silvana Muchsinati; Jollin; Adineka Fatyandri; Teh Zaharah Yaacob (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research aims to analyze the influence of Green Hiring, Green Training, Green Empowerment and Green Participation on Environmental Performance, Health and Safety as mediating variables. This research was conducted on employees of manufacturing companies that have ISO 14001 and ISO 45001 in Batam City with 381 respondents. The data management method is PLS-SEM. Results showed that nine hypotheses were accepted and four hypotheses were not accepted. The research results show that Green Hiring, Green Training, Green Empowerment, and Green Participation positively affects on Health and Safety. Green Empowerment and Green Participation positively affects on Environmental Performance. Green Hiring and Green Training do not show a significant influence on Environmental Performance. Health and Safety positively affects on Environmental Performance. Mediating role occurs in Green Empowerment, and Green Participation in Environmental Performance by Health and Safety. However, Green Hiring and Green Training were not successfully mediated by Health and Safety.